2014
DOI: 10.5812/ircmj.20749
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Ovine Embryo Production: the Study of Seasonal and Oocyte Recovery Method Effects

Abstract: Background:To current knowledge, different oocyte's recovery method and various seasons have profound impact on in vitro embryo production (IVEP).Objectives:The aim of this study was to define an efficient recovery method for oocytes harvesting from slaughterhouse material in different seasons, and their effects on IVEP yield.Materials and Methods:Ovaries from slaughtered ewes in breeding season (BS) and non-breeding season (NBS) were collected from a local abattoir. The oocytes were recovered through aspirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Thus, the development rate, ranging between 12.28% in pregnant females and 21.82% in non-pregnant hinds on the 4th day of the cycle, is dependent on the reproductive status. The differences in the development rate of blastocysts have been shown previously by Dadashpour Davachi et al, who obtained higher efficiency with the ewes in the breeding season, compared with the females in anestrous phase [40]. Nevertheless, the opposite results in which the blastocyst development rates were independent of the season were presented in sika deer by the laparoscopic ovum pick-up, ranging from 22% to 34% of the total oocytes during the non-breeding and breeding seasons [41].…”
Section: Discussionmentioning
confidence: 65%
“…Thus, the development rate, ranging between 12.28% in pregnant females and 21.82% in non-pregnant hinds on the 4th day of the cycle, is dependent on the reproductive status. The differences in the development rate of blastocysts have been shown previously by Dadashpour Davachi et al, who obtained higher efficiency with the ewes in the breeding season, compared with the females in anestrous phase [40]. Nevertheless, the opposite results in which the blastocyst development rates were independent of the season were presented in sika deer by the laparoscopic ovum pick-up, ranging from 22% to 34% of the total oocytes during the non-breeding and breeding seasons [41].…”
Section: Discussionmentioning
confidence: 65%
“…As proved in our study, several investigators indicated higher oocyte yield in breeding than in nonbreeding season. In this respect, Dadashpour et al (2014) found that the number of goat oocytes recovered by different collection methods was higher in breeding than in non-breeding season. Also, Majeed et al (2015) reported that recovery rate was higher (87.3%) in breeding season than in non-breeding one (72.5%).…”
Section: Ovarian Characteristicsmentioning
confidence: 93%
“…In this way, Farag et al (2010) recorded higher proportion of COCs and improved oocyte yield/ovary in sheep during spring than in winter and summer. In goats, the highest recovered oocyte yield was found in the breeding season, irrespective of recovery technique (Dadashpour et al, 2014). In sheep, COCs percentage was lower (P<0.05) in winter than in summer (Seydou et al, 1999;Gou et al, 2009).…”
Section: Oocyte Categorymentioning
confidence: 99%
See 2 more Smart Citations